Anti-inflammatory Effect of a Novel Pectin Polysaccharide From Rubus chingii Hu on Colitis Mice - Kong, Yuanfang; Hu, Yulong; Li, Jieming; Cai, Juntao; Qiu, Yuanhao; Dong, Chunhong (Frontiers in Nutrition, 2022)
Rubus chingii Hu has been used as a functional food for a long time. A novel pectin polysaccharide named RCHP-S from Rubus chingii Hu was structural identification and explored the anti-inflammatory effect on colitis mice. RCHP-S was composed of mannose, rhamnose, glucuronic acid, galacturonic acid, glucose, galactose and arabinose. NMR spectroscopy and methylation analysis showed that RCHP-S was mainly composed of HG-type pectin domains, but also contains a small amount of RG-I. The anti-inflammatory tests indicated that the mouse macrophage RAW 264.7 cells were pretreated with RCHP-S could show a significant inhibitory effect on the mRNA level of iNOS, IL-1β, IL-6 and TNF-α in vitro. Polysaccharide RCHP-S reduced the enteritis symptoms in dextran sulfate sodium (DSS)-induced colitis mice by inhibiting inflammatory factors released. These results indicated that the Rubus chingii Hu polysaccharide can be used as food additives for the treatment of intestinal inflammation.